Rethinking Adult Toy Play in the Age of Ludic Liberation: Imaginative, Visual and Social Object-Interactions of Mature Players - Heljakka Katriina (France, 2022)
This paper challenges the readers to rethink adult toy play by demonstrating evidence for the rich and multifaceted nature of contemporary adult toy play cultures. It is based on a ten-year period of extensive research among mature toy players and illustrates the necessity of a shift in thinking about the user-groups of toys. The paper as a think piece bases on long-term, rigorous research, and argues for the need to acknowledge adult toy play as an important and growing area of contemporary toy cultures. It summarizes the work of a toy researcher interested in adult toy relations (conducted between years 2008-2018) and has a two-way agenda: By turning to cultural phenomena related to ludification and toyification of culture, it functions both as a cultural analysis of the ludic Zeitgeist, as well as a mapping of what has been learned about adult play in contemporary toy cultures so far. The case studies featured in this paper have been grounded in multiple readings and analyses of the manifestations of adult toy play as presented in photoplay (or toy photography) displayed on social media, e.g. Flickr and Instagram. It is supplemented with thematic interviews and participatory observation at toy conventions. Moreover, research methods include an extensive literary review in connection with doctoral research (Heljakka, 2013) and post-doctoral studies (2014-2018), and empirical studies (based on closer visual analyses of toy collections and qualitative interviews with mature players aged between 25-50+ years) on adult toy play in reference to contemporary character toys such as doll-types Blythe (Tomy Takara), Barbie and Ken (Mattel), My Little Pony (Hasbro), and Star Wars toys (by various toy makers).
Proceedings of the 8th International Toy Research Association World Conference Toys and Material Culture: Hybridisation, Design and Consumption